Effect of the Irradiation on Optical and Electrical Properties of Triple-Junction Flexible Thin Solar Cells for Space Applications - Parravicini, Jacopo; Arcadi, Francesco; Le Donne, Alessia; Campesato, Roberta; Casale, Mariacristina; Greco, Erminio; Binetti, Simona (Frontiers in Physics, 2019)
The most common multijunction solar cell arrangement employs the InGaP/InGaAs/Ge configuration, which is usually exploited for high-efficiency space applications. We here test the reliability of a triple-junction device with an innovative low-thickness and flexible configuration: this is investigation is aimed at providing its main macroscopic features which must be taken into account for their applications. Notably, the specific optical and electrical features and the performance variation of these thin solar cells are systematically analyzed, both in begin-of-life (BOL) configuration and after irradiation (end-of-life, EOL) by either electrons or protons. Measurements of I-V curves, with correlated parameters, and of spectral responses (external quantum efficiency) are accomplished on several BOL and EOL samples: this allows to describe the inhomogeneous damage of the subjunctions and to follow the evolution of the solar cell physical quantities as a function of the kind and the amount of irradiation. Finally, photoluminescence emission spectra are measured, pointing out the effect of particle bombardment on luminescent features. Our results show that these innovative solar devices allow for the combination of high specific power, mechanical flexibility, high performance, and strong resistance to particle irradiation, making them an excellent option for space applications.